Inhalable bacteriophage powders: Glass transition temperature and bioactivity stabilization. Issue 2 (14th April 2020) - Chang, Rachel Yoon Kyung; Kwok, Philip Chi Lip; Khanal, Dipesh; Morales, Sandra; Kutter, Elizabeth; Li, Jian; Chan, Hak‐Kim
Abstract: Recent heightened interest in inhaled bacteriophage (phage) therapy for combating antibacterial resistance in pulmonary infections has led to the development of phage powder formulations. Although phages have been successfully bioengineered into inhalable powders with preserved bioactivity, the stabilization mechanism is yet unknown. This paper reports the first study investigating the stabilization mechanism for phages in these powders. Proteins and other biologics are known to be preserved in dry state within a glassy sugar matrix at storage temperatures ( T s ) at least 50°C below the glass transition temperature ( T g ). This is because at ( T g − T s ) >50°C, molecules are sufficiently immobilized with reduced reactivity. We hypothesized that this glass stabilization mechanism may also be applicable to phages comprising mostly of proteins. In this study, spray dried powders of Pseudomonas phage PEV20 containing lactose and leucine as excipients were stored at 5, 25 or 50°C and 15 or 33% relative humidity (RH), followed by assessment of bioactivity (PEV20 stability) and physical properties. PEV20 was stable with negligible titer loss after storage at 5°C/15% RH for 250 days, while storage at 33% RH caused increased titer losses of 1 log10 and 3 log10 at 5 and 25°C, respectively. The plasticizing effect of water at 33% RH lowered the T g by 30°C, thus narrowing the gap between T s and T g to 19–28°C, which was insufficient for glass stabilization. In contrast, the ( T g − T s ) values were higher (range, 46–65°C) under the drier condition of 15% RH, resulting in the improved stability which corroborated with the vitrification hypothesis. Furthermore, phage remained stable (≤1 log10 ) when the ( T g − T s ) value lay between 26–48°C, but became inactivated as the value fell below 20°C. In conclusion, this study demonstrated that phage can be sufficiently stabilized in spray dried powders by keeping the ( T g − T s ) value above 46°C, thus supporting the vitrification hypothesis that phages are stabilized by immobilization inside a rigid glassy sugar matrix. These findings provide a guide to better manufacture and storage practices of inhaled phage powder products using for translational medicines.